A comparative study on the heavy metal solidification/stabilization performance of four chemical solidifying agents in municipal solid waste incineration fly ash - Wang, Feng-He; Zhang, Fan; Chen, Ya-Jun; Gao, Jay; Zhao, Bin (Journal of hazardous materials, 2015)
•The solidification performance of four solidifying agents in fly ash were compared.•Their leachability were analyzed in accordance with different extraction procedures.•Solidifying agents with multiply hydrosulfide groups show excellent performance.•The leaching content of Cd, Ni, Pb and Zn is higher than the thresholds in China.•The excessive acetic acid makes its binding capacity stronger in HJ/T 300-2007. Investigated in this paper were the content, specification distribution, and risk assessment code (RAC) determination of six targeted heavy metals and potentially toxic metals in fly ashes from a municipal solid waste incinerator in China. Contained in it is a comparison of the solidification/stabilization performance of two novel solidifying agents of sixthio guanidine acid (SGA) and tetrathio bicarbamic acid (TBA) with sodium dimethyldithiocarbamate (SDD) and Na2S, and analysis of their leachability in accordance with TCLP 1311 of the US EPA and the extraction procedures of China (HJ/T 299-2007 and HJ/T300-2007). The total concentration of Zn, Cu, Ni, Pb, Cr, Cd is 37383.47, 3080.77, 1583.92, 1356.43, 566.15, and 77.83mg/kg, respectively. Cr (3.7%) and Pb (7.50%) pose low risk; and Ni (12.93%) and Zn (15.45%) have a medium risk; while Cu (69.84%) and Cd (82.5%) have a very high risk according to their RAC score. Compared with SDD and Na2S, SGA and TBA show an excellent overall solidifying performance due to their multiply hydrosulfide groups that bind with heavy metals very efficiently. The obtained results indicate that the leaching content of Cd, Ni, Pb and Zn is higher than the thresholds prescribed in GB5085.3-2007, and the excessive acetic acid makes its binding capacity stronger in HJ/T 300-2007 than in TCLP 1311.